-(2x+4)+6=10

Simple and best practice solution for -(2x+4)+6=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2x+4)+6=10 equation:


Simplifying
-1(2x + 4) + 6 = 10

Reorder the terms:
-1(4 + 2x) + 6 = 10
(4 * -1 + 2x * -1) + 6 = 10
(-4 + -2x) + 6 = 10

Reorder the terms:
-4 + 6 + -2x = 10

Combine like terms: -4 + 6 = 2
2 + -2x = 10

Solving
2 + -2x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -2x = 10 + -2

Combine like terms: 2 + -2 = 0
0 + -2x = 10 + -2
-2x = 10 + -2

Combine like terms: 10 + -2 = 8
-2x = 8

Divide each side by '-2'.
x = -4

Simplifying
x = -4

See similar equations:

| 1.5x=2x-59 | | 2(3(4x-5))=36 | | 9g=99 | | 6+(4/5)b=(9/10)b | | 8/-2/3 | | -x-22=3x+30 | | -x^2+2x=35 | | 2(3x+1)=10 | | 0.15y+0.07(y+6000)=1960 | | x(68)=17 | | 4(x+-7)+12=12 | | 4*3/16 | | (x+5)2=13 | | 8(4v+1)= | | 7+-16v+-9= | | 3+8/2 | | 15-5(2x+1)=-8 | | 5(1p+6)=8p | | x+3+1-9x= | | -17+x=x+22 | | G=3F+24 | | 3/8+x=5x | | 70=-3x | | p=9+1+s | | 16/8(2)x6 | | 1/3x+11+x=2-9x+14 | | 5x-2(x+4)=9 | | -4(6-7v)-2(1-5v)=12 | | -8x-77=170+5x | | 8n-3n+3= | | 4a+7a+6=0 | | 2y+2x+16=60 |

Equations solver categories